Associations between trait anhedonia and emotional memory deficits in females with schizophrenia versus major depression. Issue 2 (15th December 2015) - Olsen, Emily K.; Bjorkquist, Olivia A.; Bodapati, Anjuli S.; Shankman, Stewart A.; Herbener, Ellen S.
Abstract: Individuals with schizophrenia (SZ) and individuals with major depressive disorder (MDD) demonstrate impaired emotional memory and decreased enjoyment of pleasant experiences (e.g., anhedonia). However, it is unclear whether these impairments reflect similar or different processes in the two diagnostic groups. This study compared emotional memory performance in three groups of females – controls, MDD, and SZ. Given that physical and social trait anhedonia has been shown to differentiate course of illness and emotional functioning within each disorder, the present study also examined whether trait anhedonia related to emotional memory differently in the groups. Participants viewed emotional and neutral images and twenty-four hours later completed an incidental recognition test. SZ participants demonstrated a trend for the worst memory performance. Across all groups, high intensity and negative images were remembered most accurately, while groups were not differentially influenced by the valence of the stimuli. Physical anhedonia was predictive of reduced memory for negative stimuli across all diagnostic groups. Group specific findings indicated that higher levels of social anhedonia were predictive of poorer memory, but only in the SZ group. Effects remained significant when controlling for depressive symptoms. Results are considered in light of the differing role of anhedonia in SZ and MDD. Highlights: Participants included schizophrenia (SZ), major depressive disorder (MDD), and controls (HC). Participants completed an emotional memory task and 24 h later completed an incidental recognition test. SZ showed greater memory impairment than MDD and HC participants. Physical anhedonia predicted reduced memory for negative stimuli across all groups. Social anhedonia was predictive of memory deficits, but only in SZ participants.